1981
DOI: 10.1007/bf01320253
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of bovine rotavirus to interferon

Abstract: Using the plaque assay or the CPE test (cytopathogenic effect), we investigated the action of human, simian (rhesus), bovine and murine interferons on bovine rotavirus adapted to grow on established Rhesus monkey kidney cell line (MA 104) or Georgia Bovine Kidney cell line (GBK). Except for the murine interferon we used, which had no antiviral effect at all, the different interferons tested were clearly active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Rotavirus replication is restricted by pretreatment of permissive cells with IFN [30] Likewise, treatment of newborn calves and piglets with IFN prior to rotavirus infection suppresses virus replication and reduces disease severity [31], [32]. Detection of rotavirus infection by host PRRs results in an elevation of type I and II IFNs in children and animals [33][35].…”
Section: Rotavirus Regulation Of Innate Signal Transduction Pathwaysmentioning
confidence: 99%
“…Rotavirus replication is restricted by pretreatment of permissive cells with IFN [30] Likewise, treatment of newborn calves and piglets with IFN prior to rotavirus infection suppresses virus replication and reduces disease severity [31], [32]. Detection of rotavirus infection by host PRRs results in an elevation of type I and II IFNs in children and animals [33][35].…”
Section: Rotavirus Regulation Of Innate Signal Transduction Pathwaysmentioning
confidence: 99%
“…6). Included in this set were NSP1 proteins representing human RV strains that are common causes of infant diarrhea: KU (G1P [8]), Wa (G1P [8]), DS-1 (G2P [4]), and WI61 (G9P [8]). Thus, human RVs may encode NSP1 proteins that by and large lack the activity found for the NSP1 proteins of several animal RVs that leads to the enhanced accumulation of ␤-TrCP in our assay system.…”
Section: Irf3mentioning
confidence: 99%
“…Rotavirus (RV), the primary cause of severe dehydrating gastroenteritis in infants and young children, is sensitive to the antiviral effects of IFN (8,19,24). The RV gene 5 product, NSP1, antagonizes the innate immune response by inducing the degradation of one or more components required for the expression of type I IFN.…”
mentioning
confidence: 99%
“…Several events may contribute to the establishment and/or maintenance of rotavirus persistence. In fact, production of defective interfering particles during rotavirus infection and susceptibility of bovine isolates to interferon (Dagenais et al, 1981), although at present not correlated with virus persistence, have been observed. Furthermore, inability of the virus to shut down the host synthetic machinery and genetic resistance of the cells to the infecting virus have been verified as causes of persistence induction in two different experimental models .…”
Section: Effects Of Fcs On a U-bek Cell Proliferationmentioning
confidence: 92%